2021
DOI: 10.1111/eci.13482
|View full text |Cite
|
Sign up to set email alerts
|

Lactation as a programming window for metabolic syndrome

Abstract: The concept of developmental origins of health and disease (DOHaD) was initially supported by the low birth weight and higher risk of developing cardiovascular disease in adult life, caused by nutrition restriction during foetal development. However, other programming windows have been recognized in the last years, namely lactation, infancy, adolescence and even preconception. Although the concept has been developed in order to study the impact of foetal calorie restriction in adult life, it is now recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 135 publications
(306 reference statements)
1
21
0
2
Order By: Relevance
“…Lactation represents a critical window of development, and adequate/optimal nutrition during this period may be overriding for the future metabolic health of the offspring, including the prevention of possible harmful programming effects due to adverse fetal conditions [ 41 ]. There is compelling evidence from intervention studies in animal models on the essential role of leptin ingested during lactation in the prevention of obesity and other related pathologies in adulthood since it ensures a correct programming and development of hypothalamic structures involved in energy metabolism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactation represents a critical window of development, and adequate/optimal nutrition during this period may be overriding for the future metabolic health of the offspring, including the prevention of possible harmful programming effects due to adverse fetal conditions [ 41 ]. There is compelling evidence from intervention studies in animal models on the essential role of leptin ingested during lactation in the prevention of obesity and other related pathologies in adulthood since it ensures a correct programming and development of hypothalamic structures involved in energy metabolism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic interconnections between the gut microbiota and certain mechanisms are implicated in MetS of developmental origins. These core mechanisms include aberrant activation of the RAAS, oxidative stress, NO deficiency and dysregulated nutrient sensing signals [ 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 ].…”
Section: Gut Microbiota and Mets Of Developmental Originsmentioning
confidence: 99%
“…Notably, different environmental insults in early life can program similar features of MetS, proposing a commonality of mechanistic pathways behind MetS of developmental origins. Despite these pathogenic mechanisms underlying developmental programming are still inconclusive, several common mechanisms have been reported, including nitric oxide (NO) deficiency, oxidative stress, aberrant activation of the renin-angiotensin-aldosterone system (RAAS), dysfunctional nutrient sensing signals, epigenetic regulation and gut microbiota dysbiosis [ 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–8 ] Although the specific mechanisms involved are only partially understood, [ 9 ] milk quality may represent one of the key factors. [ 10 ] Thus, intervention studies in rodents have shown that the intake of an obesogenic diet during the perinatal period negatively affects the structure and function of the mammary gland and therefore the composition of milk, [ 11 ] including altered metabolism‐regulating hormones and fatty acids (FA) profiles. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%